Efektivitas Program Kampung Hortikultura dalam Pemberdayaan Wanita di Kecamatan Ilir Timur II Kota Palembang - Sriati Sriati; Thirtawati Thirtawati; Oleg Salengko (Seminar Nasional Lahan Suboptimal, 2018)
Sriati et al, 2019. Effectiveness of “Kampung Hortikultura” Program in Women Empowerment at Ilir Timur II Subdistrict Palembang City. pp. 322-332.Program of ‘Kampung Hortikultura’ is one of PT Pusri CSR program especially for supporting empowerment group namely Kelompok Posdaya Gemilang at  Ilir Timur II  Subdistrict  Palembang City. The objectives of this research were (1) to measure the effectiveness of the CSR program of  PT. PUSRI, (2) to analyze the level of housewife’s work productivity in Ilir Timur II Subdistrict Palembang, (3) to analyze the relationship of ‘Kampung Hortikultura’ program effectiveness with level of housewife’s work productivity. Survey method was used to observe and collect data. Simple random sampling with random table was used to observe 30 samples from 114 populations of housewife who follow the program. The collected data was processed using SPSS 16.00. Result of the research show that (1) Kampung Hortikultura program was on medium criteria effective on average score of 30,10 (66,89% from ideal score) which was shown the program goals has been successfully on five indicator, namely participation, time, quantity and pragram continuity. (2) the level of housewife’s work productivity  of program participant was shown on high score category at average score 20,47 (75,81% from ideal score), (3) there were significant positive correlation between program effectiveness with level of housewife’s work productivity at Ilir Timur II Subdistrict Palembang City, with the Rank Spearman correlation coeficient (Rs ) =0,744 at a =0,05.